2017
DOI: 10.3758/s13423-017-1285-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence buffers the effect of physiological arousal on dishonesty

Abstract: We studied the emotional processes that allow people to balance two competing desires: benefitting from dishonesty and keeping a positive self-image. We recorded physiological arousal (skin conductance and heart rate) during a computer card game in which participants could cheat and fail to report a certain card when presented on the screen to avoid losing their money. We found that higher skin conductance corresponded to lower cheating rates. Importantly, emotional intelligence regulated this effect; particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…TEI did not predict physiological reactivity in two studies that used a computer game to induce stress. On both occasions, EDA and HR reactivity was unrelated to TEI (Singh and Sharma, 2012; Pittarello et al, 2018). However, the latter study also considered TEI/IQ combinations, and found that a high TEI/low IQ combination was the most detrimental to cortisol reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…TEI did not predict physiological reactivity in two studies that used a computer game to induce stress. On both occasions, EDA and HR reactivity was unrelated to TEI (Singh and Sharma, 2012; Pittarello et al, 2018). However, the latter study also considered TEI/IQ combinations, and found that a high TEI/low IQ combination was the most detrimental to cortisol reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, high-trait EI individuals are more able to deal with negative events (Sevdalis et al, 2007), to manage stress and emotions (Mikolajczak, Petrides, Coumans, & Luminet, 2009) and to increase performance in the face of failures (Agnoli, Pittarello et al, 2015). Physiological data confirm these results, finding an association between trait EI and affective arousal (Rubaltelli, Agnoli, & Franchin, 2016), and showing that trait EI can moderate the effect of arousal on behaviour (Pittarello, Conte, Caserotti, Scrimin, & Rubaltelli, 2017).…”
Section: Trait Emotional Intelligence (Trait Ei)mentioning
confidence: 86%
“…The concept of trait EI, which is defined as a constellation of emotional perceptions assessed via questionnaires and rating scales (Petrides et al 2007), suggests that individuals differ in the way they subjectively process, use, and manage affect-laden information (Petrides and Furnham 2003). Pittarello et al (2018) showed that trait EI can moderate the effect of arousal in a setting where people could cheat to obtain an economic advantage. Further, Agnoli et al (2015) showed that high trait EI individuals were more resilient to failures when they were told that their effort was not sufficient to help a needy child.…”
Section: Trait Emotional Intelligence (Ei)mentioning
confidence: 99%